Characterization of Zebu cattle breeds in Tanzania using random amplified polymorphic DNA markers - Gwakisa, P.S.; Kemp, Stephen J.; Teale, A.J. (Wiley, 2009)
A total of 141 short primers, of arbitrary nucleotide sequence, were used singly in poly‐merase chain reactions to amplify DNA fingerprints in pools of DNA representing three Zebu cattle breeds. Two primers, which discriminated between the breed‐specific DNA pools were used further to amplify individual pool components in order to establish band frequencies of the amplified fingerprints. One of the primers (ILO 1127) amplified a RAPD fingerprint in 61%of TSZ animals but less than 6% in the other breeds, while another primer (ILO 1065) revealed a DNA sequence common to 89% of the Boran animals and less than 30% in the other two breeds. Bandsharing and mean average percentage difference calculated within and between the three breeds using RAPD fingerprint data showed a higher degree of homogeneity within than across the breeds and indicated measurable divergence between the three breeds. It is concluded that RAPD polymorphisms are useful as genetic markers for cattle breed differentiation.